Identification of novel MITF mutations in Chinese families with Waardenburg syndrome type II. Issue 9 (29th July 2021) - Wang, Jing; Lu, Yu; Yan, Xiaohong; Shen, Tian; Li, Linke; Rao, Yufang; Tan, Bo; Xiong, Wenyu; Cheng, Jing; Zhao, Yu; Yuan, Huijun
Abstract: Background: Waardenburg syndrome (WS) is a rare autosomal‐dominant syndrome and is characterized by sensorineural hearing loss and pigment abnormalities. It is subdivided into four types according to the clinical characteristics. MITF is one of the major pathogenic genes for type II. The aim of this study was to investigate MITF mutations and the clinical characteristics of WS type 2 (WS2) in four Chinese families. Method: Clinical diagnoses were based on detailed clinical findings. Six WS2 patients from four unrelated Chinese families were enrolled. Massively parallel DNA sequencing was used to find pathogenic genes and Sanger sequencing was used to confirm the variants detected. Results: Sensorineural hearing loss was observed in four of six patients, three had heterochromia iridis, and five have freckled faces. We identified three novel MITF heterozygous mutations (c.831dupC, c.650G>A, and c.711‐2A>G) and one recurrent heterozygous mutation (c.328C>T) in the four WS2 families. Intra‐familial phenotypic variability and incomplete penetrance were found in WS2 patients with pathogenic variants of MITF . Conclusion: Genetic diagnosis was performed for the involved four families based on the clinical manifestations. Four heterozygous mutations were identified in the MITF gene. Our findings expanded the phenotypic and genotypic spectrum of WS. Abstract : MITF mutations and the clinical characteristics of WS2 in Chinese families. Four novel heterozygous mutations in the MITF gene. Intra‐familial phenotypic variability and incomplete penetrance in the MITF gene.